Cost-benefit of a protected cultivation system of tomato in San Quintín - Meraz Ruiz, Lino (Revista Mexicana de Ciencias Agrícolas, 2023)
This paper explains the benefits of implementing a protected cultivation system for farmers in the San Quintín Valley (Baja California, Mexico) engaged in the production of vegetables, particularly tomatoes. The importance of carrying out this research lies in the fact that the implementation of a protected cultivation system (greenhouse-shade mesh) increases production and improves the quality of tomato crops, while generating an important technological advance for the agricultural sector, allowing the obtaining of benefits for both: the farmer and the industry. The ideal sources of financing to carry out the system of this type of cultivation are also part of this writing. To this end, a methodology that involved the following two steps was developed: collection of theoretical information and data collection through a questionnaire applied to eight tomato-producing companies in the San Quintín Valley in 2020. The results infer that the majority opt for cultivation with shade mesh for the production of the products, but that in turn it is very difficult to obtain government resources. It is concluded that the shade mesh is the type of protected cultivation system with greater use, through which production can be increased and the quality of products can be improved, there are still limitations in the acquisition of government support, and it is for that reason that most use the capital of their company and the financing of a bank for its implementation.
Keywords: protected crop; tomato; San Quintin